Effects of Different Nitrogen Forms on Growth, Phenolic Content, and Antioxidant Activity in Hedychium speciosum and H. coronarium - Muenrew, Janjira; Suksathan, Ratchuporn; Puangpradab, Ratchadawan; Rachkeeree, Apinya; Kantadoung, Kuttiga (Asian Health, Science and Technology Reports, 2020)
Nitrogen (N) is the most important nutrient element for plant growth and the synthesis of many secondary metabolites. Plants typically obtain inorganic N in form of NH4+ and NO3-. Two Hedychium species were grown in nutrient solutions modified from Smart and Barko (1985). The experiment consists of three N forms; NH4+, NH4+NO3-, NO3- and control (no N form) with the same concentration of nitrogen (500 µM) for 60 days. Destructive sampling was done and morphology was recorded. Total phenolic content (TPC) was evaluated by Folin-Ciocalteu method while the antioxidant activity was evaluated by DPPH and ABTS radical scavenging activity. Different nitrogen forms have significantly (p ≤0.05) affected plant height, root numbers, root number and total biomass between two Hedychium species. H. speciosum had height new shoot, leaf number, root number and total biomass in NH4+ supply. H. coronarium had height, leaf number, root number and total biomass in NH4+NO3- supply. Total phenolic contents both species were increased by NH4+ supply. H. speciosum were accumulate total phenolic content in the leaves 21.55 mg.g-1 GAE was lower than in H. coronarium 43.49 mg.g-1GAE, but in stem of the H. speciosum were accumulate total phenolic content 25.08 mg.g-1GAE was lower than in H. coronarium 20.66 mg.g-1GAE. NH4+ supply increased antioxidant activity with DPPH radical scavenging activity and ABTS radical scavenging activity.